Sentience and animal welfare - Broom, Donald M., (CABI, 2014)
This book discusses topics on the qualities that make up sentience; ethics, morality and attitudes; animal welfare science: history and concepts; brain complexity and cognitive ability; feelings and emotions; awareness and consciousness; motivation and needs; welfare assessment; sentience during development, brain damage and old age; ethical decisions about humans and non-humans; and sustainability, welfare attitudes and education.